ANALYSIS ON LUMINANCE CONSERVING BI-HISTOGRAM EQUALISATION AND CLAHE FOR UNDERWATER IMAGE ENHANCEMENT (International Journal of Food and Nutritional Sciences, 2021)
We present a practical method in this study for improving underwater photographs that have been damaged by medium absorption and scattering. Our method uses a single picture approach and lacks technological equipment, knowledge of the aquatic environment, or understanding of scene composition. It expands on the merging of two pictures that are directly derived from an interpretation of the original degraded image that has been given colour compensation and a white balance. Edges and colour contrast are transferred to the output picture as a result of the two images to be fused, as well as the weight charts that go with them. Low vision and poor contrast are problems with photographs taken in murky watery circumstances. Therefore, there is a need to enhance imaging data from aquatic research and examination work so that it can be analysed to value the requested information. Brightness Preserving Bi- Histogram Equalisation (BBHE), a novel technique for improving contrast, is suggested in this study. The brightness enhancement of aquatic photos is greatly aided by CLAHE.